HOAX MENJADI GANGGUAN KESEJAHTERAAN MASYARAKAT: PENTINGYA IMPLEMENTASI TABAYYUN PADA MASA SEKARANG - Aqli, Zainal (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2021)
This paper discusses the mental revolution which is interpreted as a fundamental change in people’s mindset, where the study is focused on how to deal with news that are still doubtful or questionable (hoaxes), such as by re-generating tabayun (correcting) the informations. Then, this paper explores a mental revolution that focuses on tabayun culture with the perspective of Islamic religious values ​​in the Quran and correlates between mental revolution and tabayun values. The final result, it was found that this tabayun values began to erode, marked by many misunderstandings that occurred in society and tabayun had to be raised again because it could have a positive impact and tackle the hoaxes for the society, which previously had to start with a mental revolution from not caring about the truth of news to critical attitudes.